Optimal design of a solar photovoltaic tracking intergrated system - Mansor, Abdullah Sulhi (2020)
The net increase of global energy demand based on active economic development allow sustainable globalization growth and healthy fiscal condition. However, a significant increase to the existing high carbon emission in the atmosphere due to fossil fuel energy for manufacturing, production and transportation process could foresee a bad environmental issue soon if no drastic approach is discussed and taken. Renewable energy especially solar energy can play a major role to reduce the dependency on fossil fuel energy in order to permit the continuity of power generation with zero carbon emission thus mitigate above mentioned concern. Solar panel system with solar tracker allow almost 30 % increase in terms of energy generation efficiency comparing to conventional solar panel system (Adarsh, Anand, & Singla, 2015). However, the capital investment on solar panel system especially with tracking device is not cheap and solar panel system efficiencies varies upon multiple technical specifications and environment factors. This study was conducted by extracted the location data including location longitude and latitude, energy load demand, surface reflectance factor, optical depth factor and sky diffuse factor. Next the technical utilized were extracted including the solar panel efficiency, inverter efficiency and battery charging and discharging efficiency. Then the model of process flow mechanism was established to be implemented in General Algebraic Modelling System (GAMS) optimization software. Based on the modeling implemented in GAMS, in this study for 30 houses demand, the fixed tilt angle system was optimized at 0 degree with the area of 476 m2 for the total cost of 167 864 USD. This model resulted 51% more power generated with 53% more total cost needed for dual axis tracker system model compared with fixed tilt angle system of the same load and location.